2012
DOI: 10.3233/wor-2012-0765-4790
|View full text |Cite
|
Sign up to set email alerts
|

Teaching ergonomics to undergraduate physical therapy students: new methodologies and impressions of a Brazilian experience

Abstract: Being ergonomics a scientific discipline based on knowledge of several areas, it is important to use education methodologies that promote critical thinking and reflective during the educational process. The article discusses the importance of interdisciplinarity in undergraduate courses in health care in particular in disciplines that address the ergonomics issue. The aspects of the introduction of new education methodologies, as well as case studies in undergraduate courses in Brazil, are discussed in this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…This could be explained assuming that more experienced physiotherapists have probably refined their practice technique and adopted ergonomic body position more regularly, reducing exposition to overloading in thumb joints. Indeed recent researches have outlined that younger physiotherapists are not trained enough about ergonomics [30] and that an interdisciplinary approach in teaching this subject may improve results [31].…”
Section: Job Factors and Painmentioning
confidence: 99%
“…This could be explained assuming that more experienced physiotherapists have probably refined their practice technique and adopted ergonomic body position more regularly, reducing exposition to overloading in thumb joints. Indeed recent researches have outlined that younger physiotherapists are not trained enough about ergonomics [30] and that an interdisciplinary approach in teaching this subject may improve results [31].…”
Section: Job Factors and Painmentioning
confidence: 99%
“…1 2 Physical therapy (PT) students not only acquire knowledge in ergonomics but also receive sufficient training to effectively address and alleviate MSK discomfort; however, studies have shown that they still experience MSK discomfort during online classes reporting 36.4% of respondents being affected by pain, and 66.9% continued to feel MSK discomfort. [3][4][5][6] Ergonomics, which focuses on the structure and organisation of tasks to a person's surroundings, is crucial in online learning to ensure safety and improve performance. [7][8][9] Addressing educational issues by establishing a suitable environment for learning through ergonomics is critical for students' quality of life and can help reduce the onset and progression of MSK discomfort.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the identified importance of practical learning experiences, Barbosa, Pinheiro, and Câmara (2012) found that traditional instruction-based curricula is still the dominant mode in some university centers that teach ergonomics courses to healthcare professionals. These researchers suggest that ergonomics curriculum should focus on critical thinking around real-life scenarios and the needs of the community in order to stimulate critical thinking and problem-solving toward ergonomic solutions.…”
Section: Introductionmentioning
confidence: 99%